Pembangunan Infrastruktur Pertanian Melalui Pengembangan Sistem Komunikasi Menuju Transformasi Agraria - Jabar, Aryuni Salpiana; Tunda, Amin; Lusianai, Wa Ode; A.T, Megawati (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2019)
The achievement of agrarian transformation as the ultimate goal of implementing agrarian reform requires various things including the development of communication systems as part of agricultural infrastructure. Unfortunately, the development of agricultural infrastructure has been struggling with the availability of hard infrastructure such as roads, dams, irrigation channels and dikes. Meanwhile, soft infrastructure such as the construction of communication systems at the village level as the basis of agriculture is still minimal. Through analysis of various books, articles and journals as a result of research related to agrarian transformation and also the availability of agricultural communication systems as a source of data, this paper presents as a discourse arousing awareness of the importance of prioritizing the development of communication systems for the aspiration of agrarian transformation in Indonesia.Keywords: Agricurtural Infrastucture, Communication System and Agrarian Transformation.Â